Mapping of changes in microscopic strain in Alloy 600 during multi‐step applications of mechanical stress. (22nd August 2017) - Ulaganathan, J.; Carcea, A. G.; Newman, R. C.; Barabash, R. I.; McIntyre, N. S.
Abstract : An Alloy 600 C‐ring has been sequentially stressed as in a classical deformation test, and the apex of the C‐ring has been spatially mapped by Laue microdiffraction during the stress deflection sequence. The diffraction spots were analyzed to provide maps showing the distributions of deviatoric elastic deformations as they changed with increased stress. The Laue‐derived elastic strains in the stress direction, averaged over small areas at the C‐ring apex responded to stress in a classic manner expected of a system undergoing elastic and then plastic deformation. For small amounts of applied stress, maps of the strain tensor in the stress direction (εxx ) showed distributions that were reasonably homogeneous. As applied stress was increased to the elastic limit, distinct local pockets of the tensile strain tensor (εxx ) became apparent. As stress approached a maximum deformation of 10 times the elastic limit, the strain tensor distribution underwent further changes. Von Mises elastic strains were also mapped and, in general, appeared to reduce as stress is increased. The formation and distribution of geometrically necessary dislocations were also monitored. After annealing at 315 C, the εxx strain tensor values were diminished from most areas excepting those bordering some grain boundaries. Strain changes in stressed Alloy 600 C‐rings were also studied following two brief stages of accelerated aqueous corrosion at 315 C. Localized εxx strain tensor and von Mises strain values gradually diminished except for areas near grain boundaries. Copyright © 2017 John Wiley & Sons, Ltd.